Influence of 36 years of integrated nutrient management on soil carbon sequestration, environmental footprint and agronomic productivity of wheat under rice-wheat cropping system - Ranjan, Shivani; Kumar, Sanjay; Dutta, Swaraj Kumar; Padhan, Smruti Ranjan; Dayal, Parmeswar; Sow, Sumit; Roy, Dhirendra Kumar; Nath, Dibyajyoti; Baral, Kirttiranjan; Bharati, Vikram (Frontiers in Environmental Science, 2023)
A long-term field experiment was conducted to study the effects of different combinations of integrated nutrient management (INM) inorganic fertilizer and organic manures on carbon sequestration and wheat yield in a rice-wheat cropping system. The experiment consisted of 11 treatments that were replicated three times. The organic manures used in the study included farm yard manure (FYM), wheat straw (WS), and green manureing (GM) with Sesbania aculeata. The results of the experiment revealed that the application of 50% of the recommended dose of fertilizers (RDF) along with 50% nitrogen (N) through FYM during rice cultivation, and 100% RDF during wheat cultivation, led to a significant increase in soil organic carbon (SOC). Specifically, the SOC content was enhanced by 46.4% (188.229 Mmg hag -1 ) compared to using 100% RDF in both rice and wheat, resulting which resulted in a C sequesterationing rate of 0.22100.00 Mμg hag -1 soil year -1 . These increases were higher in treatments that combined organic and inorganic inputs. Additionally, the application of 50% RDF and substituting 50% of the nitrogen with FYM during wheat cultivation resulted in a 24.7% increase in grain yield compared to using 100% RDF in both rice and wheat. The integrated nutrient management (INM) treatments, which included the use of organic manures along with inorganic fertilizers, showed significantly (p ≤ 0.05) higher agronomic efficiency (AE) of nitrogen (N), phosphorus (P) and potassium (K), partial factor productivity (PFP) of N, P and K, and carbon pool index (CPI) compared to the application of inorganic fertilizers at the recommended dose. Moreover, the INM treatments also exhibited lower greenhouse gas (GHGs) emission intensity. Application of neither chemical fertilizers nor organic manure (T1) resulted in maximum GHG emission intensity (328.1 kg CO2 eq Mg -1 yield). Based on these findings, it can be concluded that the combined use of inorganic fertilizers and organic manures significantly increased crop yield and SOC sequestration while reducing GHG emissions in a rice-wheat cropping system in the eastern Indo-Gangetic Plains (EIGP) of India.